Resident Physician Experience and Duration of Electronic Health Record Use - Holmgren, A. Jay; Lindeman, Brenessa; Ford, Eric W. (Applied Clinical Informatics, 2021)
Background Electronic health records (EHRs) demand a significant amount of physician time for documentation, orders, and communication during care delivery. Resident physicians already work long hours as they gain experience and develop both clinical and socio-technical skills.Objectives Measure how much time resident physicians spend in the EHR during clinic hours and after-hours, and how EHR usage changes as they gain experience over a 12-month period.Methods Longitudinal descriptive study where participants were 622 resident physicians across postgraduate year cohorts (of 948 resident physicians at the institution, 65.6%) working in an ambulatory setting from July 2017 to June 2018. Time spent in the EHR per patient, patients records documented per day, and proportion of EHR time spent after-hours were the outcome, while the number of months of ambulatory care experience was the predictor.Results Resident physicians spent an average of 45.6 minutes in the EHR per patient, with 13.5% of that time spent after-hours. Over 12 months of ambulatory experience, resident physicians reduced their EHR time per patient and saw more patients per day, but the proportion of EHR time after-hours did not change.Conclusion Resident physicians spend a significant amount of time working in the EHR, both during and after clinic hours. While residents improve efficiency in reducing EHR time per patient, they do not reduce the proportion of EHR time spent after-hours. Concerns over the impact of EHRs on physician well-being should include recognition of the burden of EHR usage on early-career physicians.
Keywords: electronic health records; medical education; resident physicians